Evaluation of the Effect of Pre-Germination Treatment on Delonix Regia Seeds - Ogu, Odiba Emmanuel; Joshua, Efi Uwhe; Haruna, David Ephraim; Samaila, Danjuma; Hannah, Nuhu Tubasen; Patricia, Okonofua Eghe; Rebecca, Ayodele; David, Bando Christopher (Darul Yasin Al Sys, 2024)
Delonix regia (Flamboyant) is a multipurpose tree species indigenous to semi-arid regions of Sub-Saharan Africa. It is being exploited to local extinction due to high dependence for fuel wood and other uses. The present study explored different pre-treatment methods for enhancing seed germination and growth of Delonix regia (Flamboyant) in Taraba State, Northern Nigeria. The experiment employed a 4 × 4 factorial design with seeds subjected to four pre-treatments (50% sulphuric acid concentration, 98% sulphuric acid concentration, cold water and hot water) at four pre-treatment time durations. Number of germination and plant height varied significantly between pre-treatments with cold water treatment recording the highest plant height (3.5cm) and the 98% sulphuric acid concentration recording the least (1.3cm). Germination rate had a moderate positive relationship with plant height. The study recommends seed immersion in cold water for 48 h as the most efficient pre-treatment for Delonix regia (Flamboyant).